CORPORATIVE SYSTEMS AND TECHNOLOGIES FOR AUTOMATIZATION OF LIBRARIES IN BELARUS - R. V. Griganets; G. O. Lauzhel; E. V. Stepantsova (Informatika)
The paper presents a composition of works performed in the framework of projects for the creation and development of the corporative library automatization system in Belarus. The systems and the automation technologies of library and information activities implemented in these projects are considered.